Mechanical Slaughtering in Islam and European countries & its relevant Newer Issues: A shariah Perspective - Dr. Abdul Hameed; Dr. Hafiz Muhammad Nasrullah Khan (jihat-ul-islam, 2021)
The foremost condition for the acceptance of rituals is to use Halal Food. Muslims always directed by Almighty Allah to earn fair and Halal eatable products which also affect human being health. There is a prescribed format in Islam to slaughter an animal for the purpose of using its meet, the animal is declared dead if the blood remains in the body of such animal. Hand slaughter mechanism has been replaced by mechanical slaughter mechanism which shocked Muslims, living in such societies where hand slaughter is prohibited by law, as it contains many controversial issues like saying the name of Almighty Allah upon slaughtering a huge quantity of animal at once whether it is permissible, as some time the animal may dies before it could be slaughtered because of electrical shocks given to it in order to relief the animal from pain of slaughtering. This study aims to conduct such issues from Islamic perspective through drawing line between Islamic and currently new invented slaughtering mechanism.